2018
DOI: 10.1016/j.ceramint.2018.06.252
|View full text |Cite
|
Sign up to set email alerts
|

Sintering effect on microstructural evolution and mechanical properties of spark plasma sintered Ti matrix composites reinforced by reduced graphene oxides

Abstract: Ti matrix composites reinforced with 0.6 wt.% reduced graphene oxide (rGO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 37 publications
6
19
0
Order By: Relevance
“…Thus, TiC is formed in situ by the reaction between Ti and C during sintering, which is consistent with the aforementioned SEM and TEM results. A similar occurrence was observed by Dong et al [28]. The intensity of TiC increases with an increase in GO content.…”
Section: Resultssupporting
confidence: 88%
“…Thus, TiC is formed in situ by the reaction between Ti and C during sintering, which is consistent with the aforementioned SEM and TEM results. A similar occurrence was observed by Dong et al [28]. The intensity of TiC increases with an increase in GO content.…”
Section: Resultssupporting
confidence: 88%
“…Therefore, it is potential to prepare the mixed powder with GO uniform dispersion by solution mixing method, which can avoid the damage of graphene structure. Dong et al [ 24 ] discovered that GO sheets effectively absorbed on the surfaces of spherical Ti particles by mechanically stirring GO and pure Ti powder in water. Our previous study also suggested that the agglomeration and structural damage of GO can be avoided by mixing GO and titanium alloy powder in anhydrous ethanol [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, graphene-reinforced Ti-matrix composites are mainly focused on pure Ti [ 16 , 17 , 18 , 19 , 20 , 24 ], Ti6Al4V [ 26 , 27 , 28 ] and TiAl [ 29 ] so far. Very little attention was paid on the influence of graphene or GO on microstructure and mechanical properties (especially tensile properties at high temperature) of high-temperature titanium alloys, which have complex microstructure evolution and high initial strength because of numerous solid solution elements.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of nano-powders, which suffer from extensive grain growth during conventional sintering, SPS is particularly suitable for the consolidating of the powders. In the literature, several works have been devoted to fabricating graphene-reinforced nanocomposites by the SPS process [143,144,145].…”
Section: Fabrication Of Mmncs Reinforced By Graphenementioning
confidence: 99%